Induction of bradyzoite-specific Toxoplasma gondii antigens in gamma interferon-treated mouse macrophages. - Bohne, W (1993)
By using stage-specific monoclonal antibodies, an in vitro model has been developed to analyze the kinetics of expression of stage-specific antigens during the conversion process between tachyzoites and bradyzoites of Toxoplasma gondii. Following infection of murine macrophages with bradyzoites, the expression of bradyzoite-specific antigens declined, whereas the expression of tachyzoite-specific antigens increased during the first 72 h postinfection. Conversely, in gamma interferon-treated murine macrophages infected with tachyzoites, the inhibitory effect of gamma interferon on replication of parasites was accompanied by the induction of bradyzoite-specific antigens.